2006
DOI: 10.1177/1524838005285916
|View full text |Cite
|
Sign up to set email alerts
|

Family Violence in the Military

Abstract: Family violence, including both child maltreatment and spouse abuse, is a public health concern in both military and civilian populations. However, there is limited knowledge concerning violence in military families relative to civilian families. This literature review critically reviews studies that examine child maltreatment and spouse abuse among military families and compares family violence in military versus nonmilitary populations. Physical abuse and neglect compose the majority of the reported and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Significantly more research has been conducted in other national contexts, in particular the USA (see, for example, the review of the literature by Rentz et al [2006]), where studies suggest that abuse is more prevalent and severe in military than civilian families (103). In the UK, young British male veterans are more likely than civilians to be convicted of violent offences (MacManus et al, 2013), most commonly violence within a domestic setting (NAPO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly more research has been conducted in other national contexts, in particular the USA (see, for example, the review of the literature by Rentz et al [2006]), where studies suggest that abuse is more prevalent and severe in military than civilian families (103). In the UK, young British male veterans are more likely than civilians to be convicted of violent offences (MacManus et al, 2013), most commonly violence within a domestic setting (NAPO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…IPV certainly occurs in military families [7,8], where it potentially has special significance [9]. For example, the prevalence of IPV could be different from that of the general population [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the prevalence of IPV could be different from that of the general population [8]. Factors favoring perpetration of IPV by military personnel could include their male predominance, their relative youth, and higher risk of heavy alcohol consumption (with the latter being seen in some [10,11] but not all [12] military organizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combat experience is believed to be a risk factor for family maltreatment (Rentz et al, 2006;Sheppard, Malatras, & Israel, 2010). Supporting this belief, studies using aggregate data found that periods with increased military deployments were associated with increased child maltreatment in military families (e.g., McCarroll, Fan, Newby, & Ursano, 2008;Rentz et al, 2007).…”
mentioning
confidence: 97%